Knowledge, attitudes, and practices toward bioterrorism preparedness among nurses: a cross-sectional study - Tiantian Li; Chao Zhao; Yongzhong Zhang; Song Bai; Zichen Zhou; Nan Li; Lulu Yao; Shaotong Ren; Rui Zhong (BMC, 2024)
Abstract Background Bioterrorism is an important topic in the field of biosecurity. Nurses, the largest group of healthcare workers, play a critical role in addressing the threat of bioterrorism. This study aimed to examine the present level of bioterrorism knowledge, attitudes, and practices among nurses. It also explored the relationships among bioterrorism knowledge, attitudes, and practices, as well as demographic variables that influence the scores of each dimension. Methods A descriptive correlational research design was conducted using a convenience sample of 429 nurses in five tertiary general hospitals in Tianjin. Registered nurses with six months or more of work experience, currently still working in hospitals, and volunteering to participate in the study are included; otherwise, they are excluded. A structured questionnaire with four components was used: sociodemographic characteristics, knowledge of bioterrorism, attitudes toward bioterrorism, and practices related to bioterrorism. The acquired data were analyzed using the Mann‒Whitney test, Kruskal‒Wallis test, Spearman correlation analysis, and multiple linear regression. This study followed the STROBE guidelines. Results The study ultimately included 429 valid surveys. The mean score for bioterrorism knowledge was satisfactory (33.06 ± 4.87), the mean score for bioterrorism attitudes was good (23.83 ± 5.23), and the mean score for bioterrorism practices was poor (10.94 ± 6.51). There was a significant negative correlation between bioterrorism knowledge and attitudes (r=-0.38, p < 0.01), knowledge and practices (r=-0.42, p < 0.01). Bioterrorism practices were significantly positively correlated with attitudes (r = 0.21, p < 0.01). Educational level (β = 0.17, p < 0.001), years of experience (β = 0.26, p < 0.001), and previous bioterrorism education (β = 0.19, p < 0.001) influenced the bioterrorism knowledge score. Gender (β=-0.21, p < 0.001), educational level (β = 0.10, p < 0.05), and previous bioterrorism education (β = 0.22, p < 0.001) affected the bioterrorism attitude score. Years of experience (β=-0.28, p < 0.001) and previous bioterrorism education (β = 0.13, p < 0.01) had an impact on the practice score. Conclusions Knowledge of bioterrorism was significantly negatively correlated with attitudes and practices, which could be attributed to the specificity of bioterrorism itself. To improve nurses' bioterrorism preparedness, continuing medical education efforts must be strengthened, as well as regular delivery of bioterrorism-specific training and drills.